Versorgung von Patienten mit Tumorschmerzen in hausärztlichen Praxen in Deutschland = Care of patients with cancer pain in general practices in Germany - Engeser, Peter; Laux, Gunter; Szecsenyi, Joachim; Krug, Katja; Leutgeb, Rüdiger (Der Schmerz, 2016)
BackgroundIn line with the increased life expectancy of people in Germany, the probability of falling ill with a malignant disease is continuously increasing. About 480,000 people in Germany contract cancer every year. One of the most important symptoms of a malignant disease is pain. Between 40 and 100% of patients with advanced cancer suffer from pain. The aim of this investigation is to show how German general practitioners care for these patients using analgetics.Materials and methodsThe data were extracted from the CONTENT database (CONTinuous morbidity registration Epidemiologic NeTwork) of the Department of General Practice and Health Services Research at the University Hospital in Heidelberg. This database has data from more than 200,000 patients and more than 3 million physician/patient contacts. The prescriptions were classified using the ATC code.ResultsPatients experiencing pain from cancer received all kinds of analgetic drugs. The data comprises 9752 prescriptions for 1362 patients. There were 4975 (51.1 %) prescriptions for Class 1 analgesics, 929 (9.5 %) for Class 2 analgetics and 1918 (19.7 %) prescriptions for Class 3 analgetics. Coanalgetics were prescribed 1930 (19.7 %) times. 1,167 patients (85.7 %) were treated in the correct manner according to the guidelines of the World Health Organisation and 195 (14.3 %) were not.ConclusionsMost GPs in Germany follow the principles of WHO structured pain therapy. However, further improvement of the results may be achieved through intensive training of colleagues.
Gesehen am 14.08.2019